2023
DOI: 10.3389/fpsyg.2023.1062148
|View full text |Cite
|
Sign up to set email alerts
|

The effect of explicit and implicit online self-compassion interventions on sleep quality among Chinese adults: A longitudinal and diary study

Abstract: ObjectiveThis study aimed to investigate the effects of explicit and implicit online intervention methods for self-compassion on improving sleep quality among Chinese adults.MethodsA total of 328 adult participants were recruited to complete the Pittsburgh Sleep Quality Questionnaire and Self-compassion Scale, and 168 participants were randomly assigned to one of three different conditions: two self-compassion intervention groups (self-compassion writing intervention asked participants to write several sentenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…A more recent online intervention self‐compassion intervention program called Resilience and Enhancement in Sport, Exercise, & Training (RESET; Kuchar et al., 2023) found that college athletes experienced greater increases in self‐compassion, and both self‐rated and coach‐rated perceived sport performance, as well as decreases in self‐criticism, depression, anxiety, and stress compared to a waitlist control group. These findings along with previous research showing that self‐compassion interventions result in improved sleep quality in non‐athlete college and adult samples (Butz & Stahlberg, 2018; Sheng et al., 2023), provide support for self‐compassion training as a potentially relevant and important resource for promoting mental health and sleep health in college athletes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A more recent online intervention self‐compassion intervention program called Resilience and Enhancement in Sport, Exercise, & Training (RESET; Kuchar et al., 2023) found that college athletes experienced greater increases in self‐compassion, and both self‐rated and coach‐rated perceived sport performance, as well as decreases in self‐criticism, depression, anxiety, and stress compared to a waitlist control group. These findings along with previous research showing that self‐compassion interventions result in improved sleep quality in non‐athlete college and adult samples (Butz & Stahlberg, 2018; Sheng et al., 2023), provide support for self‐compassion training as a potentially relevant and important resource for promoting mental health and sleep health in college athletes.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies with non‐athlete college students have demonstrated that higher self‐compassion is associated with shorter sleep onset latency (Hu et al., 2018), reduced sleep disturbances (Teixeira et al., 2016), and improved sleep quality (Greeson et al., 2014; Hu et al., 2018; Semenchuk et al., 2022). Moreover, self‐compassion intervention studies have been shown to improve sleep quality in student, adult, and clinical populations (Butz & Stahlberg, 2018; Sheng et al., 2023). These findings have been consolidated recently in two meta‐analyses demonstrating negative and moderate associations between self‐compassion and sleep difficulties (Brown et al., 2021; Butz & Stahlberg, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, a questionnaire scale such as the SCS measures self-compassion by presenting the concept of self-compassion itself (e.g., "be kind to yourself") and then asking the participants to rate themselves on whether they fit the concept. Presenting the self-compassion concept in this way may serve as a kind of priming to participants or cause them to have some preconceived notion [41]. In East Asia, including Japan, where self-criticism is sometimes considered a virtue and the SCS score is lower than the West [42], self-compassion is an unfamiliar concept and may serve as a more robust primer.…”
Section: The Study's Contributionmentioning
confidence: 99%